Accuracy and Repeatability of Internet-ordered Spectacle Lenses. Issue 12 (December 2021) - Gordon, Adam; Twa, Michael D.; Cutter, Gary; Kleinstein, Robert N.
Abstract : SIGNIFICANCE: Both consumers and eye care practitioners need to know how well online optical vendors conform with the accepted standards for quality and safety. We found that almost 1 in 10 prescriptions failed to meet national standards, which is a significant improvement over previous studies. PURPOSE: The purpose of this study was to assess the accuracy and repeatability of spectacle lens prescriptions ordered from a sample of online vendors. METHODS: Spectacle lens prescriptions were ordered by paid participants with no optical training who were masked to the study objectives. The prescription powers ordered (sphere, cylinder, and axis) were statistically sampled from 1000 previously filled prescriptions. A total of 100 orders were placed with each of three online vendors that included a range of high- and low-powered single vision lenses and progressive addition lenses, and duplicate orders to assess repeatability. An independent certified testing laboratory was contracted to assess conformance with voluntary consensus standards (ANSI Z80.1-2015) and Food and Drug Administration drop-ball safety testing. Lenses not meeting these standards were counted as failures. RESULTS: The overall failure rates for the three vendors were 11.2 ± 3.2% (vendor A), 8.0 ± 2.7% (vendor B), and 8.2 ± 2.8% (vendor C). The repeatability for 20 prescriptions ordered five times from each vendor was high, with correlation coefficients greater than 90%. There were no observed lens impact failures. CONCLUSIONS: Almost 1 in 10 spectacle lens prescriptions ordered from three online vendors failed to meet national standards for optical quality. Additional studies are needed to assess eyewear ordered online for other important patient-specific variables that can influence visual performance and ultimate acceptability of prescription eyewear, such as lens placement relative to the visual axis, frame fit, and cosmetic acceptability.